2006
DOI: 10.1111/j.1741-3737.2006.00237.x
|View full text |Cite
|
Sign up to set email alerts
|

Parents and Peers in Relation to Early Adolescent Problem Behavior

Abstract: Concurrent and prospective associations between parent‐youth dyadic hostility and adolescent externalizing and internalizing problem behavior were examined in a sample of 416 families. Parenting control, parents’ well‐being, and youths’ affiliation with deviant peers were included as integral covariates. Information from multiple sources was analyzed using structural equation modeling. Concurrently, youth externalizing problems were associated with dyadic hostility, deviant peers, inadequate parenting control,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
0
10

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 48 publications
(47 reference statements)
7
78
0
10
Order By: Relevance
“…It seems that higher parent-adolescent conlict is related to greater exhibition of negative outward behavior, such as aggressiveness and delinquent acts, and internalizing symptomatology. Conversely, the opposite efect was found in other studies wherein dyadic hostility was not associated with youth internalizing symptoms [53].…”
Section: Parent-adolescent Conlictmentioning
confidence: 45%
See 1 more Smart Citation
“…It seems that higher parent-adolescent conlict is related to greater exhibition of negative outward behavior, such as aggressiveness and delinquent acts, and internalizing symptomatology. Conversely, the opposite efect was found in other studies wherein dyadic hostility was not associated with youth internalizing symptoms [53].…”
Section: Parent-adolescent Conlictmentioning
confidence: 45%
“…Parent-child conlict is often found to be a predictor of adolescent externalizing symptomatology [26,27,53]. Eichelsheim et al found that the negative quality of the parent-adolescent relationship, characterized by recurring discord and negative arguments between the parent and the adolescent, was strongly related to the adolescents' levels of aggression, concluding that the negative and coercive interaction paterns in the parent-adolescent relationship seem to sprawl directly into adolescent interpersonal aggression [25].…”
Section: Parent-adolescent Conlictmentioning
confidence: 99%
“…According to Giordano (1995), peer relations are attractive to adolescents for realizing a sense of belonging because they are more egalitarian, less controlling, and less judgmental than relations with adults. Reflecting this, peers become increasingly important as ''socializing agents'' (Buehler, 2006;Fuligni & Eccles, 1993). Indeed, adolescents' behavior is highly influenced by their friends' behavior.…”
Section: Unsupervised Wanderingmentioning
confidence: 99%
“…This influence includes maladaptive outcomes, such as antisocial behavior (Patterson, Forgatch, Yoerger, & Stoolmiller, 1998;Stoolmiller, 1994). It has been consistently shown that the number of delinquent friends is one of the strongest correlates of delinquent behavior in adolescence (Buehler, 2006;Laird, Pettit, Dodge, & Bates, 2005). Yet it has to be acknowledged that these Overview of hypotheses to be tested.…”
Section: Unsupervised Wanderingmentioning
confidence: 99%
“…While there has been an increase in research on Asian American (AA) developmental, ecological, and cultural contexts. Moreover, the quality of the parent-child relations can have a significant effect on adolescents' well-being and functioning (Buehler, 2006;Parke & Buriel, 2006;WalkerBarnes & Mason, 2004). As such, research shows a strong association between AA adolescent-parent relationship and adolescents' emotional or psychological well-being and behavioral functioning (Greenberger & Chen, 1996;Hwang, Wood, & Fujimoto, 2010;Kim, Chen, Wang, Shen, & Orozco-Lapray, 2012;Lee & Liu, 2001;Lim, Yeh, Liang, Lau, & McCabe, 2009;Qin, 2008;Ying & Han, 2007).…”
Section: Introduction1mentioning
confidence: 99%